(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines the concept of Inclusive Education, which aims to ensure that all learners, regardless of their physical, cognitive, social, or cultural differences, have equitable access to quality education. The paper analyzes theoretical foundations, pedagogical practices, and policy frameworks that support inclusivity in classrooms. Key themes include differentiated instruction, universal design for learning, teacher attitudes and preparedness, and social-emotional support for diverse learners. Challenges such as resource limitations, systemic barriers, and teacher training are also discussed. The study concludes that inclusive education requires not only curricular and instructional adaptations but also a shift in educational culture toward equity, respect, and empowerment.